Organizational innovation: Interactive role of external knowledge strategies and market dynamisms - Maryam Haji Ali Beigi (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2021)
There are different determinants for organizational innovation. By taking an encompassing look into dynamics of organizational innovation, this paper examines how organizational innovation is an outcome to interaction of knowledge search strategies and underlying market conditions. Although the role of knowledge management capabilities on organizational innovation have been studied in literature but the effects of external knowledge strategies as an external KM enabler on different parts of organizational innovation has not been covered. To fill that gap and to capture deep dynamics of organizational innovation this paper analyzes the relationship between external knowledge diversity and organizational innovation under the influence of competition intensity and uncertain demand trends which is the second contribution of this study. It is demonstrated that the effects of competition intensity or uncertain demand trends on organizational innovation are diminished through their interactive manifestation with knowledge search diversity. By applying quantile regression in different levels, we additionally indicate that such diminishing effect varies among different industries depending on their organizational innovation intensity as the third novel analytics of this paper.
Keywords: 330; Organizational innovation; External Search diversity; Competition intensity; Uncertaindemand